IMPROVING THE QUALITY OF ENGLISH IN MEDICINE (Journal of Universal Science Research, 2023)
Effective communication is crucial in the medical field, and good English plays a vital role. Join us as we delve into the importance of medical English, explore common mistakes to avoid, and provide valuable tips for improvement. Together, let's enhance patient care through enhanced communication. Mastering the language of medicine requires understanding key words and terminology. We'll guide you through an essential list of medical terms, from anatomy to pharmaceuticals, helping you build a solid foundation in medical English.